Ethyl Acetate와 Methanol을 이용한 블루베리 추출물 대사체 분석 - 조영희(Young-Hee Jo); 김수경(Sugyeong Kim); 권다애(Da-Ae Kwon); 이홍진(Hong Jin Lee); 최형균(Hyung-Kyoon Choi); 어중혁(Joong-Hyuck Auh) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
Metabolite profiling of blueberry (cultivar "Spartan") was performed by extraction using different solvents, methanol and ethyl acetate, through metabolomic analysis using LC-MS/MS. Unsupervised classification method (PCA) and supervised prediction model (OPLS-DA) provided good categorization of metabolites according to the extraction solvents. Metabolites of the anthocyanin family, including delphinidin hexoside, delphinidin, 5-O-feruloylquinic acid, malvidin hexoside, malvidin-3-arabinoside, petunidin-3-arabinoside, and petunidin hexoside, were mainly detected in methanol fractions, whereas those of the flavonoid family, including chlorogenic acid, chlorogenic acid dimer, 6,8-di-C-arabinopyranosyl-luteolin, and luteolin were successfully prepared in the ethyl acetate fraction. Thus, metabolomic analysis of blueberry extracts allows for the simple profiling of whole and distinctive metabolites for future applications. 본 연구에서는 LC-MS/MS를 이용한 블루베리의 methanol과 ethyl acetate 추출 분획에 존재하는 대사체의 분석을 통해 효율적인 대사체 profiling의 가능성을 탐색하였다. LC-MS/MS에서 검출되는 대사체를 통계 처리한 결과, methanol 추출 분획에서는 5-O-feruloylquinic acid, malvidin hexoside, malvidin-3-arabinoside, petunidin-3-arabinoside, delphinidin hexoside, delphinidin, petunidin hexoside와 같은 안토시아닌 계열의 화합물들이 존재하였고, ethyl acetate 분획에서는 chlorogenic acid, chlorogenic acid dimer, 6,8-di-C-arabinopyranosylluteolin, luteolin과 같은 플라보노이드 계열의 화합물이 검출되었다. 본 연구는 기존 연구와 달리 대사체학 기법을 이용한 블루베리 추출물 전체 대사물질의 profiling을 시도한 최초의 연구로서 블루베리에 함유된 유용 성분의 스크리닝 등 향후 응용 연구에 유용한 기반으로 이용될 수 있을 것으로 기대된다.